On an Average Goldbach Representation Formula of Fujii - Goldston, D A; Ade, Irma Suriajaya (arXiv.org, 2022)
Fujii obtained a formula for the average number of Goldbach representations with lower order terms expressed as a sum over the zeros of the Riemann zeta-function and a smaller error term. This assumed the Riemann Hypothesis. We obtain an unconditional version of this result, and obtain applications conditional on various conjectures on zeros of the Riemann zeta-function.